The Pseudomonas aeruginosa CrcZ RNA interferes with Hfq-mediated riboregulation. - Elisabeth Sonnleitner; Konstantin Prindl; Udo Bläsi (PLoS ONE)
The RNA chaperone Hfq regulates virulence and metabolism in the opportunistic pathogen Pseudomonas aeruginosa. During carbon catabolite repression (CCR) Hfq together with the catabolite repression control protein Crc can act as a translational repressor of catabolic genes. Upon relief of CCR, the level of the Hfq-titrating RNA CrcZ is increasing, which in turn abrogates Hfq-mediated translational repression. As the interdependence of Hfq-mediated and RNA based control mechanisms is poorly understood, we explored the possibility whether the regulatory RNA CrcZ can interfere with riboregulation. We first substantiate that the P. aeruginosa Hfq is proficient and required for riboregulation of the transcriptional activator gene antR by the small RNA PrrF1-2. Our studies further revealed that CrcZ can interfere with PrrF1-2/Hfq-mediated regulation of antR. The competition for Hfq can be rationalized by the higher affinity of Hfq for CrcZ than for antR mRNA.